The Effect of Company Size, Profitability, Liquidity, Leverage, Sales Growth on Company Value - Adam Erlangga; Kartika Hendra Ts; Supawi Pawenang (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study aims to test and analyze the influence of company size, profitability, liquidity, leverage, and sales growth on company value.The research method in this study is quantitative. The data source in this study is the official website of the Indonesia Stock Exchange. Meanwhile, the research period was taken for 5 years from 2020 to 2024. The population and sample used were Transportation & logistics companies listed on the IDX for the period 2020 - 2024. The technique used in this study was Purposive Sampling with certain criteria. The techniques used were observation methods and documentation methods in the form of financial reports listed on the IDX throughwww.idx.co.idfor 5 years. The data analysis techniques used were statistical analysis, namely multiple linear regression, F test, t test, and coefficient of determination. The research results show that company size, profitability, liquidity, and sales growth have no effect on company value. However, leverage does.